ST8SIA4-Dependent Polysialylation is Part of a Developmental Program Required for Germ Layer Formation from Human Pluripotent Stem Cells. (3rd May 2016) - Berger, Ryan P.; Sun, Yu Hua; Kulik, Michael; Lee, Jin Kyu; Nairn, Alison V.; Moremen, Kelley W.; Pierce, Michael; Dalton, Stephen
Abstract: Polysialic acid (PSA) is a carbohydrate polymer of repeating α-2, 8 sialic acid residues that decorates multiple targets, including neural cell adhesion molecule (NCAM). PST and STX encode the two enzymes responsible for PSA modification of target proteins in mammalian cells, but despite widespread polysialylation in embryonic development, the majority of studies have focused strictly on the role of PSA in neurogenesis. Using human pluripotent stem cells (hPSCs), we have revisited the developmental role of PST and STX and show that early progenitors of the three embryonic germ layers are polysialylated on their cell surface. Changes in polysialylation can be attributed to lineage-specific expression of polysialyltransferase genes; PST is elevated in endoderm and mesoderm, while STX is elevated in ectoderm. In hPSCs, PST and STX genes are epigenetically marked by overlapping domains of H3K27 and H3K4 trimethylation, indicating that they are held in a "developmentally-primed" state. Activation of PST transcription during early mesendoderm differentiation is under control of the T-Goosecoid transcription factor network, a key regulatory axis required for early cell fate decisions in the vertebrate embryo. This establishes polysialyltransferase genes as part of a developmental program associated with germ layer establishment. Finally, we show by shRNA knockdown and CRISPR-Cas9 genome editing that PST-dependent cell surface polysialylation is essential for endoderm specification. This is the first report to demonstrate a role for a glycosyltransferase in hPSC lineage specification.